Negative Politeness Strategies in What Would You Do? TV Show - Meidiana Suyono; Erna Andriyanti (Journal of Language and Literature, 2021)
Being polite is significant to maintain good communications as well as social relationship and therefore various strategies are applied to show language politeness. This sociopragmatic study deals with negative politeness found in What Would You Do? TV show to describe the types of negative politeness strategies and investigate the reasons of choosing those strategies. This research applied a descriptive qualitative approach supported by statistics. The data were in the form of utterances containing negative politeness strategies, sourced in the conversations and the scripts between the participants and the actors. There were 106 data collected by note-taking technique from the show’s YouTube channel. The trustworthiness was attained through analyst triangulation. The findings show that seven negative politeness strategies are used by the participants in their responses to the actors: Being Indirect (12), Questions, Hedges (40), Minimizing the Imposition (12), Apologizing (25), Giving Difference (9), Being Pessimistic (6), and State the FTA as General Rule (2). The dominance of Questions, Hedges relates to the options provided to the addressee to accept or refuse the speaker’s request and to make utterances sound more polite. Related to reasons, the payoffs factor was dominant (with 84 occurrences) because it is the basic factor the participants might think about what they will get by applying a certain strategy. The circumstances factor has 22 occurrences, consisting of social distance (14), social power (5), and rank of imposition (3).